Identification of determinants in the protein partners aCBF5 and aNOP10 necessary for the tRNA:Ψ55-synthase and RNA-guided RNA:Ψ-synthase activities - Muller, Sébastien (Oxford University Press, 2007)
Protein aNOP10 has an essential scaffolding function in H/ACA sRNPs and its interaction with the pseudouridine(Ψ)-synthase aCBF5 is required for the RNA-guided RNA:Ψ-synthase activity. Recently, aCBF5 was shown to catalyze the isomerization of U55 in tRNAs without the help of a guide sRNA. Here we show that the stable anchoring of aCBF5 to tRNAs relies on its PUA domain and the tRNA CCA sequence. Nonetheless, interaction of aNOP10 with aCBF5 can counterbalance the absence of the PUA domain or the CCA sequence and more generally helps the aCBF5 tRNA:Ψ55-synthase activity. Whereas substitution of the aNOP10 residue Y14 by an alanine disturbs this activity, it only impairs mildly the RNA-guided activity. The opposite effect was observed for the aNOP10 variant H31A. Substitution K53A or R202A in aCBF5 impairs both the tRNA:Ψ55-synthase and the RNA-guided RNA:Ψ-synthase activities. Remarkably, the presence of aNOP10 compensates for the negative effect of these substitutions on the tRNA: Ψ55-synthase activity. Substitution of the aCBF5 conserved residue H77 that is expected to extrude the targeted U residue in tRNA strongly affects the efficiency of U55 modification but has no major effect on the RNA-guided activity. This negative effect can also be compensated by the presence of aNOP10.